Wages Against Artwork : Decommodified Labor and the Claims of Socially Engaged Art - La Berge, Leigh Claire (Book collections on Project MUSE., 2019)
The last twenty years have seen a rise in the production, circulation, and criticism of new forms of socially engaged art aimed at achieving social justice and economic equality. In Wages Against Artwork Leigh Claire La Berge shows how socially engaged art responds to and critiques what she calls decommodified labor--the slow diminishment of wages alongside an increase in the demands of work. Outlining the ways in which socially engaged artists relate to work, labor, and wages, La Berge examines how artists and organizers create institutions to address their own and others' financial precarity; why the increasing role of animals and children in contemporary art points to the turn away from paid labor; and how the expansion of MFA programs and student debt helps create the conditions for decommodified labor. In showing how socially engaged art operates within and against the need to be paid for work, La Berge offers a new theorization of the relationship between art and contemporary capitalism.